Pengaruh Tanggung Jawab Sosial Perusahaan terhadap Komitmen Organisasi dan Kinerja Karyawan - Hamdani, Anwar; Awatara, I Gusti Putu Diva (Jurnal Aplikasi Manajemen, 2016)
Abstract: Not much research focuses on corporate social responsibility toward commitment of employees. This study aims toanalyze the influence of corporate social responsibility toward Employee Performance and the role of organization commitment in mediating the effect of corporate social responsibility toward Employee Performance. This research was exploratory research based on primary data. Primary data was collected from professional employees who work in different organizations. The population in this study is the professional employees of different organizations or institutions where such organization or institution has been carrying out CSR activities in the city of Surakarta. The sample in this study amounted to 100 employees using simple random sampling technique. The analysis technique used in this research is the path analysis; hypothesis testing using t-test, F test and coefficient of determination. The results showed that corporate social responsibility (CSR) and the commitment of the organization can affect the performance of employees so that social responsibility becomes very important in helping improve the welfare of employees so that impact employee commitment to the organization increases and gives a good reputation for the company to provide benefits competitive and create the maximum employee performance.